2016
DOI: 10.1620/tjem.240.215
|View full text |Cite
|
Sign up to set email alerts
|

Early Pregnancy Factor Enhances the Generation and Function of CD4<sup>+</sup>CD25<sup>+</sup> Regulatory T Cells

Abstract: The mechanisms of fetal semi-allograft acceptance by the mother's immune system have been the target of many immunological studies. Early pregnancy factor (EPF) is a molecule present in the serum of pregnant mammals soon after conception that has been reported to have immunomodulatory effects. In the present study, we aimed to determine whether immune cells such as CD4 + CD25 + regulatory T cells (Tregs) are involved in the suppressive mechanism of EPF. Accordingly, CD4 + CD25 -T cells were isolated from splee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Early pregnancy factors that inhibit T-cell-induced rosette formation were reported to be detected just after fertilization [111]. Later, several substances, such as platelet activating factor, thioredoxin, and chaperonin 10, were proposed as early pregnancy factors [112][113][114]. It was also reported that the embryo-derived pre-implantation factor (PIF), a novel embryo-specific 18-kDa peptide that is specifically expressed on the fetus and placenta [115], was secreted at the two-cell stage and was able to be detected in the maternal sera prior to implantation [116].…”
Section: Regulation Of Endometrial Receptivity and Embryo Invasion Bymentioning
confidence: 99%
“…Early pregnancy factors that inhibit T-cell-induced rosette formation were reported to be detected just after fertilization [111]. Later, several substances, such as platelet activating factor, thioredoxin, and chaperonin 10, were proposed as early pregnancy factors [112][113][114]. It was also reported that the embryo-derived pre-implantation factor (PIF), a novel embryo-specific 18-kDa peptide that is specifically expressed on the fetus and placenta [115], was secreted at the two-cell stage and was able to be detected in the maternal sera prior to implantation [116].…”
Section: Regulation Of Endometrial Receptivity and Embryo Invasion Bymentioning
confidence: 99%
“…For almost 2 decades, the nature of the factor mediating this response eluded investigators, but it was finally determined to share homology with chaperonin 10, a member of the heat shock/chaperonin protein family that participates in protein folding and stabilization in a wide array of cellular contexts (Cavanagh, 1996;Morton, 1998). Chaperonin 10 (also known as HSP10 and HSPE1) is expressed in a wide array of cell types and has been shown to modulate immune cell function, for example, by inducing formation of Treg cells and production of IL10 and TGFB (Chen et al, 2016). The role that HSP10 plays in ruminant pregnancy is yet unclear.…”
Section: Peripheral Immune Responses To the Conceptusmentioning
confidence: 99%
“…Maternal–fetal tolerance is achieved through different mechanisms such as an increase of Treg cells, expression of CD274 (PD-L1) in the trophoblastic tissue, and an increase of Breg cells (21, 22). Early pregnancy factor enhances Treg-cell production and IL-10 and TGF-β expression in splenocytes from female mice (23). In pregnant mice, the increase in Breg is necessary to avoid immunological abortion.…”
Section: Introductionmentioning
confidence: 99%